PENGARUH STANDAR OPERASIONAL PROSEDUR DAN KUALITAS KEHIDUPAN KERJA (Quality Of Worklife) TERHADAP EFEKTIFITAS KERJA (Studi Pada Universitas Perjuangan Tasikmalaya) - Salgangga, Selji (JURNAL EKONOMI PERJUANGAN, 2023)
This research is motivated by the existence of several problems, including the effectiveness of the work of employees at the University of Perjuangan Tasikmalaya which is still low, this is thought to be caused by the not optimal implementation of SOP carried out by the university so that the work results of employees are not in accordance with the provisions set. In addition, the quality of work life is not supportive so that there are still employees who have not been able to complete a job according to the set time. The purpose of this study was to determine the effect of standard operating procedures and quality of work life on work effectiveness at the University of Perjuangan, Tasikmalaya City. In this study used a descriptive method with a quantitative approach. Respondents in this study were employees at the University of Perjuangan Tasikmalaya as many as 132 people so the authors took samples using simple random sampling technique so that the number of samples in this study were 57 people. Analysis was carried out on the data collected both from the results of observations, interviews, and questionnaires. The data analysis stage begins with validity, reliability, transformation of ordinal values ​​into intervals, and verivicative/quantitative data analysis.   Keywords: Standard Operating Procedures, Quality of Work Life, Work Effectiveness